Judgment, decision-making and success in sport - Bar-Eli, Michael; Plessner, Henning; Raab, Markus; Wiley InterScience (Online service) (Malden, MA : Wiley, 2011)
"Judgment, Decision-Making and Success in Sport presents a thorough overview and assessment of the study of Judgment and Decision-Making (JDM) in sports psychology, and represents an important source of information for those interested in the possible causes and reasons for success and failure in sport ... The only book to apply the principles of JDM to sport. Applies theory to practice by looking at problems of athletes, coaches, and referees and providing recommendations for dealing with them. Offers an overview of current JDM research. Useful for psychologists, physical education teachers, sports scientists, and researchers in this field."--
"Judgment, Decision-Making and Success in Sport introduces the fundamental approaches of Judgment and Decision-Making (JDM) research in psychology and applies them directly to a variety of JDM problems in sport"--
Judgment and Decision Making as a Topic of Sport Science -- --Maximization and optimization in sport -- JDM history -- The development of JDM research in sport -- Rationale and structure of this book -- -- Theories of (Social) Judgment -- -- Psychophysics -- Social Judgment Theory -- Social cognition -- Summary -- -- Theories of Decision Making -- -- Subjective Expected Utility Theory -- Prospect Theory -- Decisional Field Theory -- Simple heuristic approach -- Summary -- -- Expertise in JDM -- -- What are the components of expertise in JDM? -- How can we measure JDM expertise? -- How can we explain JDM expertise? -- How can we develop JDM expertise? -- Summary -- -- Athletes -- -- Judging one's own performance -- What choices are athletes confronted with? -- How do athletes choose? -- JDM training for athletes -- Summary -- -- Managers and Coaches -- JDM as a leadership task -- Managerial JDM -- Coaches' JDM -- -- Referees -- -- The tasks of referees -- Perceptual limitations -- Prior knowledge -- Rules of information integration -- Improving referees' JDM -- -- Observers -- -- Biases in judgments of sport performance -- Predictions and betting.
Includes bibliographical references and index.
Print version record.
Keywords: Sports -- Psychological aspects; SPORTS & RECREATION -- Sports Psychology; Sports -- Psychological aspects; Sportpsychologie; Sport; Oordeel; Besluitvorming; Electronic books; Electronic books